Competition and Financial Stability: A new Paradigm - FIRANO, Zakaria; FILALI, Fatine (Journal of Advanced Studies in Finance, 2020)
From the Nineties, the Moroccan banking system knew several reforms which contributed to the liberalization and the deregulation of banks. The objective is to arrive to a banking sector resilient, competitive, developed and making it possible to increase the surplus of the borrowers and the depositors. Although the relation between competition and financial stability is discussed, this paper proposes to formulate a new explanation of this relation while being based on the trilogy: competition, concentration and stability (CCS). Initially we develop the model of Panzar and Rose (1982, 1987) to measure the competition of the dynamic banking system since 1993. Then, a data model of panel was estimated, highlighting the nonlinear relation between financial stability and banking competition. The checking of this relation made it possible to propose a new design concerning the relation between financial stability and competition. Indeed, the results obtained with through an optimization model affirm that this relation is cyclic, in the direction where, a stronger competition supports financial stability in situation of strong impact strength, on the other hand, in a situation of financial instability, more competition worsens the situation of the banking system.